Effect of a novel quaternary ammonium silane on dentin protease activities. (March 2017) - Daood, Umer; Yiu, Cynthia; Burrow, Michael F.; Niu, Li-Na; Tay, F.R.
Abstract: Objectives: Demineralized dentin collagen release C-terminal cross-linked telopeptide (ICTP) and C-terminal peptide (CTX) during degradation. The present study evaluated the effects of dentin pre-treatment with K21, a quaternary ammonium silane (QAS), on matrix metalloproteinase (MMP) and cathepsin K-mediated collagen degradation. Methods: Dentin beams were demineralized with 10% H3 PO4 for 24 h. After baseline dry mass measurements, the beams were divided into 5 groups (N = 10) according to protease inhibitors. The beams were pre-treated for 2 min with 2% chlorhexidine (CHX), 2%, 5% or 10% QAS; no pre-treatment was performed for the control group. The beams were subsequently incubated in calcium- and zinc-containing medium for 3, 7 or 14 days, after which changes in dry mass were measured and incubation media were examined for ICTP and CTX release. The MMP-2 and cathepsin K activities in QAS-treated dentin powder were also quantified using ELISA. Results: The two factors (disinfectants and time) had a significant effect on dry mass loss, ICTP and CTX release (p < 0.001). The percentage of dry mass loss increased with time and was significantly lower in all experimental groups when compared to the control at 14 days (p < 0.001). Conversely, the rate of ICTP and CTX release was significantly lower in the experimental groups, compared to the uninhibited control at 7 and 14 days (p < 0.001). Dentinal MMP-2 and cathepsin K activities were significantly reduced after demineralized dentin was pre-treated with QAS. Conclusion: The experimental QAS is a good inhibitor of MMP and cathepsin K activities in demineralized dentin. Clinical significance: The newly developed antibacterial quaternary ammonium silane increases the resistance of dentin collagen to degradation by inhibiting endogenous matrix metalloproteinases and cysteine cathepsins. The quaternary ammonium silane cavity disinfectant is promising for use as a protease inhibitor to improve durability of resin-dentin bonds.